Novel TLR7/8 agonists promote activation of HIV-1 latent reservoirs and human T and NK cells - Li, Yangyang; Wang, Zhisong; Hou, Ying; Liu, Xiaoyu; Hong, Junxian; Shi, Xuanling; Huang, Xiaojie; Zhang, Tong; Liao, Xuebin; Zhang, Linqi (Frontiers in Microbiology, 2023)
Antiretroviral therapy can successfully suppress HIV-1 replication to undetectable levels but fails to eliminate latent and persistent HIV-1 reservoirs. Recent studies have focused on the immunomodulatory agents such as Toll-like receptor 7 and 8 (TLR7 and TLR8) capable of activating, thereby rendering the reservoir susceptible to antiretroviral inhibition and immune recognition and elimination. In this context, this study focused on generating a diverse repertoire of TLR7/8 agonists to identify more potent candidates for activating latent HIV-1 and immune cells’ response. Through combinational strategies of computer-aided design and biological characterization, 159 pyrido [3,2-d] pyrimidine and pyridine-2-amine-based derivatives were synthesized. Of which, two TLR7/8 dual and one TLR8-specific agonists with exceptionally high potency in activating HIV-1 latent reservoirs in cell lines and PBMCs of patients with persistent and durable virologic controls were identified. Particularly, these agonists appeared to enhance NK and T cells activity, which were correlated with the degree of surface activation markers. The outcome of this study highlights the remarkable potential of TLR7/8 agonists in simultaneously activating HIV-1 from the latently infected cells and augmenting immune effector cells.